Historical dictionary of American education - Altenbaugh, Richard J. (Greenwood Press, 1999)
This reference work contains over 350 entries. Topics include biographies of significant national and regional leaders and reformers, important ideas, events, institutions, agencies and trends that helped to shape American policies and perceptions regarding education.